Ordering of factors that influence the choice of rational organizational and technological solutions for the use of polyvinyl chloride (PVC) window system in the restoration of architectural monuments - OSIPOV, Alexander; BONDARENKO , Mykola (Ways to Improve Construction Efficiency, 2025)
The study and systematization of influencing factors is an extremely important stage in determining the most effective and rational system for selecting the use of polyvinyl chloride (PVC) windows. It should be noted that PVC window structures are among the most efficient solutions due to their combination of energy efficiency, technological capabilities, durability, and economic feasibility. From an environmental perspective, the potential of this material exceeds expectations, as it can be easily recycled and reused in the production of both profiles and other PVC-based materials. PVC can be reprocessed 6 to 10 times without losing its properties. It is also important to emphasize that this is a modern and technologically advanced material that significantly extends the service life and preservation level of residential architectural heritage sites. However, the choice of a specific rational system for applying PVC window systems depends on a complex set of factors. The most significant among them are the architectural and historical value of the heritage site, the types and methods of restoration, construction conditions, and various restrictions. It is essential to highlight that comprehensive research and analysis of these factors ensure the rationality of decisions made both for a particular object and for the field as a whole. Discussions regarding the use of modern materials in the restoration of architectural monuments continue both in Ukraine and abroad—particularly in Western European countries, where the concentration of heritage sites requiring maintenance and restoration is the highest. Therefore, research in this field has practical significance for optimizing the process of selecting a rational system for applying PVC windows in architectural monuments. Ultimately, this contributes to improved energy efficiency, including in residential buildings with heritage status, enhances preservation opportunities for future generations, and better satisfies the growing needs of property owners and residents for improved comfort and living conditions.